Chronic Pseudoparalysis Needs to Be Distinguished From Pseudoparesis: A Structural and Biomechanical Analysis. Issue 2 (February 2021) - Ernstbrunner, Lukas; El Nashar, Rany; Favre, Philippe; Bouaicha, Samy; Wieser, Karl; Gerber, Christian
Background: Chronic pseudoparalysis is generally defined as the inability to actively elevate the arm above 90° with free passive range of motion and no neurological deficits. It has been suggested that this arbitrary cutoff needs to be refined. Purpose: To analyze whether there are structural and biomechanical differences in patients with chronic pseudoparalysis and those with chronic pseudoparesis. Study Design: Case-control study; Level of evidence, 3. Methods: In this retrospective study, 50 patients with chronic massive rotator cuff tears (mRCTs; ≥2 tendons) and free passive and active scapular plane abduction <90° were divided into 2 groups: pseudoparalysis group (n = 24; active scapular plane abduction, <45°) and pseudoparesis group (n = 26; active scapular plane abduction, >45° and <90°). Radiographic measurements included the critical shoulder angle, acromiohumeral distance, posterior acromial tilt, anterior and posterior acromial coverages, and posterior acromial height on outlet views. Measurements on magnetic resonance imaging (MRI) included fatty infiltration of the rotator cuff muscles, anterior (subscapularis) and posterior (infraspinatus/teres minor) tear extensions, and global (anterior + posterior) tear extension in the parasagittal plane. A published musculoskeletal model was used to simulate the effect of different mRCTs on the muscle force required for scapular plane abduction. Results: Plain radiographs revealed no differences between patients with chronic pseudoparalysis and those with pseudoparesis. MRI assessment showed significant differences between patients with chronic pseudoparalysis and those with pseudoparesis with respect to fatty infiltration of the subscapularis (2.9 vs 1.6; P < .001) and infraspinatus (3.6 vs 3.0; P < .001) muscles, and anterior (−23° vs 4°; P < .001), posterior (−23° vs −14°; P = .034), and global rotator cuff (225° vs 190°; P < .001) tear extensions. The anterior tear extension in patients with chronic pseudoparalysis always involved more than 50% of the subscapularis, which was associated with an odds ratio of 5 for inability to actively abduct more than 45°. The biomechanical model was unable to find a combination of muscles that could balance the arm in space when the tear extended beyond the supraspinatus and the cranial subscapularis. Conclusion: This study confirms that chronic pseudoparalysis and pseudoparesis are associated with different structural lesions. In the setting of a chronic mRCT, involvement of more than 50% of the subscapularis tendon with fatty infiltration of stage 3 is associated with pseudoparalysis of active scapular plane abduction <45°. The key function of the subscapularis was confirmed in the biomechanical model.